Effect of Sand Wetting on Physically Hardened Moulding Sands Containing a Selected Inorganic Binder. Part 2 - Stachowicz M.; Granat K.; Pałyga Ł. (Archives of Foundry Engineering, 2016)
In the paper, an attempt is made to explain the previously observed increased effectiveness of utilising hydrated sodium water-glass grade 137 after hardening moulding sands with selected physical methods. In the modified process of preparing sandmixes, during stirring components, water as a wetting additive was introduced to the sand-binder system. Presented are examination results of influence of faster microwave heating and slower traditional drying of the so-prepared moulding sands on their tensile and bending strength, calculated per weight fraction of the binder. The measurement results were confronted with SEM observations of linking bridges and with chemical analyses of grain surfaces of high-silica base. On the grounds of comprehensive evaluation of hardened moulding sands, positive effects were found of the applied physical process of binder dehydration and presence of the wetting additive. It was observed that introduction of this additive during stirring, before adding the binder, improves flowing the binder to the places where durable linking bridges are created. It was also found that the applied methods of hardening by dehydration enable creation of very durable linking bridges, strongly connected with the sand base, which results in damages of high-silica grain surfaces, when the bridges are destroyed.